Potret Kesenjangan Pembelajaran Jarak Jauh - Fa’uzobihi, Fa’uzobihi; Tjalla, Awaluddin; Indrajit, Richardus Eko (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This article aims to evaluate the impact of long-range pursuit programs using the Disscrepancy Model, developed by Malcolm Provus. Emphasizes the view of gaps in program implementation. The word discrepancy means gap, this model according to Madaus, Sriven & Stufflebeam (1993: 79-99) departs from the assumption that to find out the feasibility of a program, evaluators can compare what should be expected to happen (standard) with what actually happens (performance). . Comparing the two things, it can be seen whether there is a gap (discrepancy), namely the standard set with the actual performance. This model was developed by Malcolm Provus, aims to analyze a program whether the program is worth continuing, increasing, or terminating. teaching evaluation is a component in the teaching system, while the teaching system itself is an implementation of the curriculum, as an effort to create classroom learning. Oemar Hamalik (2001: 145) states, the evaluation process is generally student-centered. This means that evaluation is intended to observe student learning outcomes and seeks to determine how learning opportunities are. From the two opinions above, the evaluation is intended to observe a teaching process, which includes the role of the teacher, teaching strategies, curriculum materials, and learning principles applied to teaching.